Experimental study of aerodynamic characteristics and evaluation of wind flow concentrator efficiency - Horobets, Valeriy; Trokhaniak, Viktor; Masiuk, Mykola; Spodyniuk, Nadia; Sheremetynska (Gorobets), Oksana; Shelimanova, Olena (My University, 2022)
Запропонована конструкція концентратора вітрових потоків дає можливість підвищити ефективність вітротурбіни і отримувати електричну енергію при малих швидкостях вітру, коли лопатеві вітротурбіни не генерують електричну енергію. Проведено верифікацію експериментальних даних з даними чисельного моделювання гідродинаміки в концентраторі вітрових потоків. Проведена оцінка використання концентатора вітрових потоків для підвищення ефективності вітрогенераторів з вертикальною віссю обертання. The proposed design of the wind flow concentrator makes it possible to increase the efficiency of the wind turbine and receive electric energy at low wind speeds, when the bladed wind turbines do not generate electricity. Verification of experimental data with data of numerical modeling of hydrodynamics in the wind flow concentrator is carried out. The evaluation of the use of wind flow concentrator to increase the efficiency of wind turbines with a vertical axis of rotation is carried out.
Keywords: концентратор; аеродинаміка; криволінійний канал; конфузор; concentrator; aerodynamics; curvilinear channel; кафедра економіки праці та менеджменту